Children's perceptions of maternal hostility as a mediator of the link between discipline and children's adjustment in four countries - Jennifer E. Lansford (2018)
Using data from 195 dyads of mothers and children (age range = 8-12 years; M = 10.63) in four countries (China, India, the Philippines, and Thailand), this study examined children's perceptions of maternal hostility as a mediator of the links between physical discipline and harsh verbal discipline and children's adjustment. Both physical discipline and harsh verbal discipline had direct effects on mothers' reports of children's anxiety and aggression; three of these four links were mediated by children's perceptions of maternal hostility. In contrast, there were no significant direct effects of physical discipline and harsh verbal discipline on children's reports of their own anxiety and aggression. Instead, both physical discipline and harsh verbal discipline had indirect effects on the outcomes through children's perceptions of maternal hostility. We identified a significant interaction between perceived normativeness and use of harsh verbal discipline on children's perception of maternal hostility, but children's perception of the normativeness of physical discipline did not moderate the relation between physical discipline and perceived maternal hostility. The effects of harsh verbal discipline were more adverse when children perceived that form of discipline as being nonnormative than when children perceived that form of discipline as being normative. Results are largely consistent with a theoretical model positing that the meaning children attach to parents' discipline strategies is important in understanding associations between discipline and children's adjustment, and that cultural context is associated with children's interpretations of their parents' behavior. © The Author(s) 2010.